Transparency, Accountability, and Public Participation as Pillars of Good Governance: Evidence from Public Administration in Indonesia - Rohmawati, Tatik; Sutisna, Yayah; Nathanael, Ricky; Mentari , Resa (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2026)
The objective of this study is to examine how the application of transparency, accountability, and participation takes place within the public administration system of Indonesia and determine the influence of all three concepts on good governance and public trust in the government institutions.  Qualitative research method will be applied in this case, involving a literature review and policy analysis to examine regulatory frameworks and innovations in the area of public administration at both national and regional levels in Indonesia. The results show that information transparency, accountability of public sector, and participation of citizens play an important role in the improvement of the efficiency of the administrative process and democracy in the country. Nevertheless, there are some issues related to the resistance of bureaucracy, lack of digitalization in some parts of Indonesia and civic participation in other regions. It is important to develop institutional mechanisms, digital governance and participation platforms to improve the quality of governance.